Efektivitas intervensi edukasi mobile phone terhadap penurunan tekanan darah pada pasien stroke - Prasetya, Ganjar Kundi; Yunitri, Ninik; Agung, Rizki Nugraha; Rayasari, Fitrian (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Stroke is one of the causes of death, most of which is caused by high blood pressure. There are still many patients who are less concerned about hypertension cases resulting in strokes when being treated, it is felt that continuous education is needed regarding knowledge and compliance. Purpose: To determine the effect of mobile phone educational intervention on reducing blood pressure in stroke patients. Method: A literature study of meta-analyze articles using the AMSTAR checklist Based on the scimago journal ranking, it entered Q1 with an impact factor of 3.593. With the G Power application, 6 samples were obtained and Jamovi 2.3.28 software was used for data processing. There were 12 educational themes based on SHEMA delivered via WhatsApp Messenger for 5 days. Results: This education was able to reduce systolic from 182 to 171, diastolic 98 to 91 and mean arterial pressure (MAP) 127 to 121. This education at least increased confidence and had productivity in controlling high blood pressure. Conclusion: The changes in systolic, diastolic and MAP reduction rates were not significant, but could control the occurrence of no increase or readmission. Keywords: Hypertension; Mobile Phone; Stroke. Pendahuluan: Stroke salah satu penyebab kematian yang sebagian besar disebabkan oleh tekanan darah tinggi. Masih banyaknya pasien kurang peduli kasus hipertensi berakibat stroke saat dirawat dirasa perlu edukasi terus menerus terkait pengetahuan maupun kepatuhan. Tujuan: Untuk mengetahui pengaruh intervensi edukasi mobile phone terhadap penurunan tekanan darah pada pasien stroke. Metode: Studi literatur dari artikel meta analysis menggunakan AMSTAR checklist, berdasarkan scimago journal ranking masuk Q1 dengan impact factor 3,593. Melalui aplikasi G Power mendapat 6 sampel dan software jamovi 2.3.28 untuk olah data. Ada 12 tema edukasi berdasar SHEMA yang disampaikan melalui whatsapp messenger selama 5 hari. Hasil: Edukasi mobile phone mampu menurunkan sistolik dari 182 menjadi 171, diastolik 98 menjadi 91, dan mean arterial pressure (MAP) 127 menjadi 121. Edukasi ini setidaknya menambah keyakinan dan memiliki produktivitas dalam pengendalian tekanan darah tinggi. Simpulan: Perubahan angka penurunan sistolik, diastolik, dan MAP tidak signifikan, tetapi dapat mengendalikan untuk tidak terjadinya peningkatan atau readmisi. Kata Kunci: Hipertensi; Mobile Phone; Stroke.